Foreign language anxiety research and the Brazilian scenario - Silveira, Fernanda Vieira da Rocha (The ESPecialist, 2020)
Over the past thirty years, the concept of foreign language anxiety (FLA) has received attention from Applied Linguistics researchers and theorists due to its relevance in the domain of foreign language teaching, learning and use. FLA has been considered the affective variable which most negatively influences foreign language learning. It is best described as a sort of situation specific anxiety, inextricably related to the learner’s feeling of apprehension and tension when using or learning the foreign language. Nevertheless, most studies focus either on FLA theory or quantitative data, which shows the necessity of more qualitative and interventional research. This article aimed to contribute to the FLA theoretical background from a transdisciplinary stance and share quantitative and qualitative intervention studies conducted in Brazil in the past twenty years.